Web-based Consulting Company Employee Timesheet - Gabriella Clara Pertiwi; Bernardinus Harnadi; Dwiyoga Widiantoro (Journal of Business and Technology, 2023)
Work timesheet is a form of work activity reporting that is usually implemented by a company to monitor the work of their employees. In this study, the researcher wanted to develop a Web-based Consulting Company Employee Timesheet which aims to facilitate the process of reporting and checking data in terms of work timesheets or reporting of work activities in a consulting company. The features developed are made in such a way that it is expected that the company's needs can be met according to the previous system of the consulting company. The method used for website application development is the waterfall method where the development stages occur sequentially. The method applied is through ERD ( Entity Relationship Diagram), Flowcharts, Use Case Diagrams, Activity Diagrams. After this web-based was created, the researchers conducted tests and interviews with admins, managers and employees of the consulting company, totaling 5 people. From the results of interviews with 5 respondents obtained a positive response to the development of a Web -based Timesheet for Consulting Company Employees.